Effects of Quark Interactions on Dynamical Chiral Symmetry Breaking by a Magnetic Field - Hiller, Brigitte (2008)
This is a contribution to the Proc. of the Seventh International Conference ''Symmetry in Nonlinear Mathematical Physics'' (June 24-30, 2007, Kyiv, Ukraine), published in SIGMA (Symmetry, Integrability and Geometry: Methods and Applications) at http://www.emis.de/journals/SIGMA/